Асимптотические оценки. Мицик М.Ф. - 9 стр.

UptoLike

Составители: 

Рубрика: 

                                                                                                              .
                                                            ,             f (x ) ≡ 1 .
αλ x = t ,
                         d                   i                                       d αλ          it 2
                                               αλ x 2
         (λ ) = ∫ f (x ) e                   2
                                                           dx =
                                                                             1
                                                                                      ∫           e dt =
                                                                                                    2

                         0                                                   αλ       0

                      ∞ it    ∞ it  
                                   2                               2
       1              e dt − e 2 dt .
                      ∫0      ∫
     =                    2
       αλ                            
                            d αλ    
                                                            ,                                             ,
                    iπ
             π 4
               e .                                                                                        ,
             2
                                            it 2
         ∞   it 2                            2         ∞                  ∞   it 2                                    ∞
                  e                                            1      dt   1       dt   2
       ∫ e dt =
              2
                −
                   it                              d
                                                           | + ∫e 2 2 ≤
                                                            αλ i d αλ t
                                                                             + ∫ 2 =
                                                                         d αλ d αλ t  d αλ
                                                                                           .
     d αλ


                                        ,
                                                   d αλ          it 2                     iπ
                                                                   π 4
                                      1
                                                       ∫    e dt =2
                                                                     e + O λ−1 .                              ( )
                                      αλ               0
                                                                   2
                                                                f (x )
                                 f ( x ) = f (0 ) + [ f ( x ) − f (0 )] = f (0 ) + xg ( x ),

                                                                       f (x ) − f (0)
                                                   g (x ) =
                                                                              x
                                                                                              [0; d ] .
                                                            iπ
                1 2π
                                                                             ( )
                                                                                          d                       i
                                                    αλ x 2
         (λ ) =      f (0) e + O λ + ∫ xg ( x ) e
                            4     −1              2
                                                           dx                                                             (14)
                2 αλ                 0

                                                                                       λ → +∞
     d                       i
                               αλ x 2
                                                 d
                                                               2i αλ x2 
     ∫ xg (x ) e                                   g ( x ) d  e
                                              1
     0
                             2
                                        dx =     ∫
                                             iαλ 0            
                                                                         =
                                                                         
                                                                         
                                  i                                      d                    i
                    αλ d 2                          αλ x 2
          g (d )e          − g (0) − ∫ g ′( x ) e
        1
     =            2                               2
                                                           dx ≤
       αλ                            0